Serious on-the-job accidents in the City of S. Paulo, Brazil - Nogueira, Diogo Pupo; Gomes, Jorge da Rocha; Sawaia, Naim (Revista de Saúde Pública, 1981)
In 1970, the Accidents On-the-Job Group of the National Institute of Social Security (INPS), began a special program for the prevention of on-the-job-accidents. The following factors were studied in 3,930 cases: age, sex, marital status, occupation, cause of accident, date of occurrence, time of occurrence, occurred how soon after beginning day's work, number and type of body lesions, limitation of working capacity.